PELAKSANAAN FUNGSI APARAT PENGAWAS INTERN PEMERINTAH (APIP) UNTUK MENUNJANG TINGKAT KEWAJARAN LAPORAN KEUANGAN PEMERINTAH KOTA MANADO - Siwy, Merry Inggrid; Saerang, David P.E.; Karamoy, Herman (Universitas Sam Ratulangi, 2016)
Internal Audit is the whole process of audit activities, the Review, evaluation, monitoring and supervisory activities other against the implementation of tasks and functions of the organization in order to provide reasonable assurance that the activities have been carried out in accordance with the benchmarks that have been set effectively and efficiently for the benefit of the leadership to Realize good governance.Accountability and transparency in the new government could be achieved if all levels of leadership controlling activities on the overall activities in their respective agencies . Internal control system ( SPI ) is a process that is integral to the actions and activities carried out continuously by the management and all employees to provide reasonable assurance on the achievement of organizational goals through effective and efficient , the reliability of financial reporting , the safeguarding of state assets, and compliance with legislation. To strengthen and support the effectiveness of internal control over the SPI made ​​implementation of tasks and functions of government agencies including state audits carried out by the internal control official Government ( APIP ) .The auditor's responsibility to detect fraud or irregularity embodied in the planning and execution to obtain reasonable assurance about whether the financial statements have been prepared in accordance with established standards.The purpose of this study was to analyze the functions of Government Internal Supervisory Apparatus (APIP) / Internal Auditor in supporting reasonable levels of Local Government Finance Report Manado City. Respondents were selected are few skilled examiner at the office of the Inspectorate of Manado. Approach Using Qualitative methods Ethnography.APIP functions that work well to prevent fraud , to produce valuable output to be input to the external auditor , the executive and the legislature to improve financial management and accountability in the area of ​​the future . Eksternal Auditor may use the results from the monitoring APIP mainly reviews the financial statements of the government , supporting the management of local government in implementing the recommendations and improvements Internal control system . APIP professional and independent encourage increased transparency and accountability in financial management to improve the fairness of the financial statements . Keywords: Government Internal Supervisory Apparatus, fraud detection, the fairness of the financial statements